A text-book of botany morphological and physiological - Sachs, Julius 1832-1897 (Cambridge University Press, 2012)
Julius Sachs was an important and influential German botanist. He attended Charles University in Prague, gaining his doctorate in 1856. After appointments in Dresden, Chemnitz and Bonn, he took a professorship at the University of Freiburg in 1867. A year later he accepted a chair at Würzburg, where he stayed for the rest of his career. Sachs made important contributions across botanical science, notably in cytology and photosynthesis. He was also largely responsible for the leap in understanding of plant physiology that took place in the second half of the 19th century. His famous Textbook of Botany, published here in the 1875 English translation of the final German edition, takes the physiological approach that he pioneered and features hundreds of instructive illustrations and a full index. It was the most influential botanical text of its day, and the standard textbook on the subject for many years.